2018
DOI: 10.3390/jmmp2030055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Process Parameter Influence in Laser Cladding of 316L Stainless Steel

Abstract: Laser Cladding is one of the leading processes within Additive Manufacturing technologies, which has concentrated a considerable amount of effort on its development. In regard to the latter, the current study aims to summarize the influence of the most relevant process parameters in the laser cladding processing of single and compound volumes (solid forms) made from AISI 316L stainless steel powders and using a coaxial nozzle for their deposition. Process speed, applied laser power and powder flow are consider… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Even though a greater number of particles was trapped at 50-60-µm particle size, from Table 3, it can be observed that the distance between the focal point and the nozzle exit was 12.59 mm, which was not optimum distance according to the experimental study conducted by various authors (Zekovic et al, 2007;Alvarez et al, 2018). The optimum distance between the focal point and the nozzle exit is around 12 mm, which is obtained for a particle size of 60-70 µm.…”
Section: Comparative Results Of Powder Particlementioning
confidence: 86%
“…Even though a greater number of particles was trapped at 50-60-µm particle size, from Table 3, it can be observed that the distance between the focal point and the nozzle exit was 12.59 mm, which was not optimum distance according to the experimental study conducted by various authors (Zekovic et al, 2007;Alvarez et al, 2018). The optimum distance between the focal point and the nozzle exit is around 12 mm, which is obtained for a particle size of 60-70 µm.…”
Section: Comparative Results Of Powder Particlementioning
confidence: 86%
“…Advantages of the laser cladding process, compared to competing processes, is that it can be used to produce complex components, offering high processing speed, high precision, potential for automation, and good repeatability. Despite a low thermal input, the technique provides a high energy density, while the heataffected zone is small [6,7,15,[17][18][19]. An important advantage of the process is the low dilution values that can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of the process is the low dilution values that can be achieved. A dilution range of 10-20% for a single pass produces depositions with good metallurgical union, satisfactory mechanical properties, and acceptable corrosion resistance [9,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Laser cladding is a material deposition technique in which a powdered or wire feedstock material is melted and solidified using a laser (light amplification by stimulated emission of radiation) to coat a substrate or produce a near-net form part, [1]. It is used to improve mechanical qualities, increase corrosion resistance, repair damaged parts, and fabricate metal composites, among other things, [2].…”
Section: Introductionmentioning
confidence: 99%